Answer:
The function rule in slope-intercept form is:
[tex]y = \frac{1}{2}x-\frac{7}{2}[/tex]
Step-by-step explanation:
The slope-intercept form of a function is given as:
[tex]y = mx+b[/tex]
Here
m is the rate of change of function and b is the y-intercept
The rate of change is calculated as:
[tex]m = \frac{difference\ in\ y}{difference\ in\ x}[/tex]
For this, any two pairs of input and output can be taken.
So using the pairs (1,-3) and (2,-1)
[tex]m=\frac{2-1}{-1+3}\\=\frac{1}{2}[/tex]
Putting the value of slope in slope-intercept form
[tex]y = \frac{1}{2}x+b[/tex]
Putting (1,-3) in the equation
[tex]-3 = \frac{1}{2}(1)+b\\-3 = \frac{1}{2}+b\\b = -3-\frac{1}{2}\\b = \frac{-6-1}{2}\\b= \frac{-7}{2}[/tex]
Putting the value of b
[tex]y = \frac{1}{2}x-\frac{7}{2}[/tex]
Hence,
The function rule in slope-intercept form is:
[tex]y = \frac{1}{2}x-\frac{7}{2}[/tex]